Method for regulating and controlling amorphous state and photoluminescence of g-C3N4 through nitrogen vacancy under high pressure

By introducing nitrogen defects under high pressure and applying pressure synergistic effect, the band gap of graphite carbon nitride (g-C3N4) is reduced, and the problem of insufficient light absorption in the visible light range is solved, and the performance is significantly improved and photoluminescent performance is achieved. enhancement.

CN119503741APending Publication Date: 2025-02-25ANQING NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411690189.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Graphite carbon nitride (g-C3N4) absorbs only light below 450 nm in the visible light range due to its wide optical band gap, limiting its light absorption and application in the visible light range.

Method used

By introducing nitrogen defects under high pressure and applying pressure synergistic action, the band gap of g-C3N4 is significantly reduced, its amorphousness is improved, and the performance of the material is regulated by adjusting the concentration and pressure of the nitrogen defect.

Benefits of technology

A significant reduction in the band gap of g-C3N4 from 2.7 eV to 2.4 eV is achieved, improving amorphousness and enhancing the photoluminescent performance of the material, providing new possibilities for its applications in the visible light range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503741A_ABST
    Figure CN119503741A_ABST
Patent Text Reader

Abstract

The invention discloses a method for regulating and controlling amorphous state and photoluminescence of g-C3N4 through nitrogen vacancy under high pressure. The preparation method specifically comprises the following steps: preparing g-C3N4 with nitrogen vacancies by adopting a KOH-assisted thermal polymerization method; applying pressure to g-C3N4 with nitrogen vacancies by using a diamond anvil cell press, wherein an amorphous phase change pressure point is continuously reduced along with the increase of the concentration of the nitrogen vacancies. The g-C3N4 prepared through the KOH-assisted thermal polymerization method is based on the nitrogen vacancy concentration and high pressure matching technology, the technical purpose of amorphous phase change regulation and control of two-dimensional graphite phase carbon nitride g-C3N4 can be effectively achieved, the application method is simple, and the regulation and control range is large.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of two-dimensional material structure regulation, and specifically relates to a method for regulating the amorphous state and photoluminescence of g-C3N4 by nitrogen vacancies under high pressure. Background Art

[0002] Graphitic carbon nitride (g-C3N4) has attracted extensive attention due to its excellent performance in efficient photocatalytic hydrogen production, CO2 reduction, water oxidation, artificial photosynthesis, and photodecomposition of organic pollutants. However, g-C3N4 has a wide optical band gap of about 2.7 eV and absorbs only light below 450 nm, which severely limits its light absorption in the visible light range and thus restricts its further applications. To overcome this problem, researchers have carried out a series of studies to adjust the band gap, including doping with heteroatoms, composite material design, nanostructures, and introducing defects or vacancies.

[0003] Among these methods, introducing defects is considered to be a suitable method because it can change the optical band gap by introducing additional energy levels. However, the optimization method of simply introducing defects has certain limitations in performance improvement and is difficult to meet higher application requirements. Therefore, it is necessary to continuously develop new strategies, explore the synergy of various methods, and further modify the performance of g-C3N4. Summary of the invention

[0004] Based on the shortcomings of the above-mentioned prior art, the present invention provides a method for regulating the amorphous state and photoluminescence of g-C3N4 by nitrogen vacancies under high pressure. The method introduces nitrogen defects into g-C3N4 and applies pressure synergistically, which can significantly reduce the band gap of two-dimensional graphite phase carbon nitride g-C3N4 material and improve amorphization. At the same time, the concentration of nitrogen defects and the size of pressure are adjusted, and the original g-C3N4 and nitrogen-deficient g-C3N4 are systematically studied. x performance.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A method for regulating the amorphous state and photoluminescence of g-C3N4 by nitrogen vacancies under high pressure comprises the following steps:

[0007] S11, fully grinding urea and KOH in a glove box protected by an inert atmosphere for 20 to 40 minutes;

[0008] S12, continuously calcining the mixture described in step S11 in a muffle furnace, then washing with distilled water to remove residues, and finally drying at 80° C. for 24 h to prepare two-dimensional graphite phase carbon nitride g-C3N4 with different nitrogen vacancy concentrations;

[0009] S13, using a diamond anvil cell apparatus to generate compressive stress on the two-dimensional graphite phase carbon nitride g-C3N4 described in step S12.

[0010] Researchers have conducted a series of studies to adjust the band gap, including doping with heteroatoms, composite material design, nanostructures, and introducing defects or vacancies. Among these methods, introducing defects is considered a suitable method because it can effectively change the performance of photocatalysts by introducing additional energy levels or acting as reaction centers. In addition, pressure, as a basic thermodynamic parameter, can change the basic properties of matter by compressing the atomic lattice without changing the composition of the material. The application of high pressure has led to a series of new phenomena, such as pressure-induced phase transitions, band gap engineering, amorphization, semi-metallization, metallization, and even superconductivity. The above steps can introduce nitrogen defects into g-C3N4, and the application of pressure works synergistically.

[0011] As a further improvement of the method of regulating the amorphous state and photoluminescence of g-C3N4 by nitrogen vacancies under high pressure.

[0012] Preferably, the mass ratio of urea to KOH in step S11 is 15:0.05-1.

[0013] The content of urea and KOH can adjust the concentration of nitrogen doping. If the doping concentration is too low, the band gap will change little, while if the doping concentration is too high, the lattice structure will be destroyed.

[0014] Preferably, the calcination temperature in the muffle furnace in step S12 is 500-700° C., and the calcination time is 4-6 hours.

[0015] The temperature and calcination time process will also affect the performance of the two-dimensional graphite phase carbon nitride g-C3N4 material. Too low a temperature will lead to insufficient nitrogen doping, and too high a temperature will cause the basic structure of the graphite phase carbon nitride g-C3N4 material to change.

[0016] Preferably, the method for generating compressive stress on two-dimensional graphite phase carbon nitride g-C3N4 in step S13 comprises the following steps:

[0017] S21. Prepare a pair of diamond and diamond base with a table diameter of 200 μm for centering and debugging, take T301 stainless steel sheet as sealing gasket, and perform a pre-pressing operation before sealing the sample;

[0018] S22, after the pre-pressing is completed, the pre-pressing indentation is punched by a laser punching device, the gasket aperture is cleaned by an ultrasonic instrument, and the sealing gasket is reset to the initial pre-pressing position as a sample cavity for loading the sample;

[0019] S23. Ruby powder is placed in the sample cavity for pressure calibration in the sample cavity. The sample is placed in the sample cavity and filled with sodium chloride powder as a pressure transmission medium.

[0020] S24. Pressurize the sample in the diamond anvil cell and use in situ high-pressure Raman spectroscopy to track the vibration mode and structural phase transition of the sample.

[0021] Preferably, the pressure range of the pressurization in step S24 is 0 to 48 GPa.

[0022] Pressure-induced amorphization is easy to maintain its stability through pressure treatment because the lack of long-range order can reduce its kinetic instability. When pressure is applied at temperatures far below the melting point or glass transition range, the crystal structure undergoes abrupt amorphization. Due to the lack of sufficient thermal energy to reach the high-pressure equilibrium crystal state, the pressure-induced amorphous state is kinetically optimal and is usually an irreversible metastable phase. Point defects, especially vacancies, can significantly reduce the stability of the primary crystal structure, thereby enhancing amorphization.

[0023] Preferably, the pressure range of the pressurization in step S24 is 15 to 24 GPa.

[0024] Under high pressure, the interlayer coupling of two-dimensional graphene carbon nitride changes under the action of pressure. When the pressure reaches about 20 GPa, a pressure-induced amorphization phase transition occurs. The pressure of the original graphene carbon nitride amorphization transition is around 25 GPa. With the introduction of nitrogen vacancies, the pressure point of the amorphization phase transition is advanced. The higher the vacancy concentration, the smaller the pressure point of the amorphization phase transition, from 24 GPa to 15 GPa, thereby realizing the regulation of the amorphous properties of the material.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] (1) The present invention can significantly reduce the band gap of two-dimensional graphite phase carbon nitride g-C3N4 material and improve amorphization by synergistically combining defects and pressure.

[0027] (2) The present invention systematically studies the original g-C3N4 and nitrogen-deficient g-C3N4 by adjusting the concentration and pressure of nitrogen defects. x performance, providing a new strategy for performance enhancement of g-C3N4.

[0028] (3) In the present invention, g-C3N4 is amorphized by inducing pressure, and this method is easy to maintain its stability through pressure treatment.

[0029] (4) In the present invention, the band gap of g-C3N4 can be reduced from 2.7 to 2.4 through the synergistic effect of nitrogen defects and pressure. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a microscopic morphology of the two-dimensional graphite phase carbon nitride g-C3N4 prepared in Example 1 under a transmission electron microscope;

[0031] Figure 2 (a) to (c) are transmission electron micrographs of the samples in comparative example 1, example 2 and example 4, respectively, and the insets are the corresponding diffraction patterns; Figure 2 (d) is the XRD pattern of the samples in Comparative Example 1 and Examples 1 to 3; Figure 2 (e) is the XPS graph of the samples in Comparative Example 1, Example 2 and Example 4;

[0032] Figure 3 The basic schematic diagram of the diamond anvil press of the present invention, wherein the numbers in the figure are: 1 is the diamond anvil; 2 is the ruby; 3 is the sealing gasket; 4 is the sample loaded in the sample chamber;

[0033] Figure 4 is the light absorption curve of the samples in Comparative Example 1 and Examples 1 to 3;

[0034] Figure 5 : is the band gap diagram of the samples in comparative example 1 and embodiments 1 to 3;

[0035] Figure 6 (a)-(d) are Raman images of the samples in Comparative Example 1 and Examples 1 to 3, respectively;

[0036] Figure 7 is the photoluminescence pressure collection curve at the center position of the samples in Comparative Example 1 and Examples 1 to 3;

[0037] Figure 8 The color change of the sample under different pressures in Example 1;

[0038] Fig. 9 It is a dotted line graph of the minimum pressure when the samples prepared in Examples 1 to 4 and Comparative Example 1 become amorphous. DETAILED DESCRIPTION

[0039] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail in combination with the embodiments below. The following content is only an example and explanation of the concept of the present invention. The technicians in the relevant technical field make various modifications or supplements to the specific implementation cases described or replace them with similar methods. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all belong to the protection scope of the present invention.

[0040] The above-mentioned preparation method of the present invention is described below through specific examples and comparative examples.

[0041] Example 1

[0042] This embodiment provides a method for regulating the amorphous state and photoluminescence of g-C3N4 by nitrogen vacancies under high pressure, comprising the following steps:

[0043] S11, fully grind 15 g of urea and 0.05 g of KOH in a glove box protected by an inert atmosphere;

[0044] S12, calcining the mixture in step S11 in a muffle furnace at 600° C. for 5 h, then washing with distilled water to remove residues, and finally drying at 80° C. for 24 h to prepare two-dimensional graphite phase carbon nitride g-C3N4 with different nitrogen vacancy concentrations;

[0045] S13, using a diamond anvil cell apparatus to generate compressive stress on the two-dimensional graphite phase carbon nitride g-C3N4 described in step S12.

[0046] The method for generating compressive stress on the two-dimensional graphite phase carbon nitride g-C3N4 in step S13 comprises the following steps:

[0047] S21. Prepare a pair of diamond and diamond base with a table diameter of 200 μm for centering and debugging, take T301 stainless steel sheet as sealing gasket, and perform a pre-pressing operation before sealing the sample;

[0048] S22, after the pre-pressing is completed, the pre-pressing indentation is punched by a laser punching device, the gasket aperture is cleaned by an ultrasonic instrument, and the sealing gasket is reset to the initial pre-pressing position as a sample cavity for loading the sample;

[0049] S23. Ruby powder is placed in the sample cavity for pressure calibration in the sample cavity. The sample is placed in the sample cavity and filled with sodium chloride powder as a pressure transmission medium.

[0050] S24. Pressurize the sample in the diamond anvil cell and use in situ high-pressure Raman spectroscopy to track the vibration mode and structural phase transition of the sample.

[0051] Example 2

[0052] The difference between this embodiment and embodiment 1 is that the amount of KOH added in step S11 is 0.1 g.

[0053] Example 3

[0054] The difference between this embodiment and embodiment 1 is that the amount of KOH added in step S11 is 0.2 g.

[0055] Example 4

[0056] The difference between this embodiment and embodiment 1 is that the amount of KOH added in step S11 is 1.0 g.

[0057] Example 5

[0058] This embodiment provides a method for regulating the amorphous state and photoluminescence of g-C3N4 by nitrogen vacancies under high pressure, comprising the following steps:

[0059] S11, fully grind 15 g urea and 0.2 g KOH in a glove box protected by an inert atmosphere;

[0060] S12, calcining the mixture in step S11 in a muffle furnace at 500° C. for 4 h, then washing with distilled water to remove residues, and finally drying at 80° C. for 24 h to prepare two-dimensional graphite phase carbon nitride g-C3N4 with different nitrogen vacancy concentrations;

[0061] S13, using a diamond anvil cell apparatus to generate compressive stress on the two-dimensional graphite phase carbon nitride g-C3N4 described in step S12.

[0062] The method for generating compressive stress on the two-dimensional graphite phase carbon nitride g-C3N4 in step S13 comprises the following steps:

[0063] S21. Prepare a pair of diamond and diamond base with a table diameter of 200 μm for centering and debugging, take T301 stainless steel sheet as sealing gasket, and perform a pre-pressing operation before sealing the sample;

[0064] S22, after the pre-pressing is completed, the pre-pressing indentation is punched by a laser punching device, the gasket aperture is cleaned by an ultrasonic instrument, and the sealing gasket is reset to the initial pre-pressing position as a sample cavity for loading the sample;

[0065] S23. Ruby powder is placed in the sample cavity for pressure calibration in the sample cavity. The sample is placed in the sample cavity and filled with sodium chloride powder as a pressure transmission medium.

[0066] S24. Pressurize the sample in the diamond anvil cell and use in situ high-pressure Raman spectroscopy to track the vibration mode and structural phase transition of the sample.

[0067] Example 6

[0068] This embodiment provides a method for regulating the amorphous state and photoluminescence of g-C3N4 by nitrogen vacancies under high pressure, comprising the following steps:

[0069] S11, fully grind 15 g urea and 0.2 g KOH in a glove box protected by an inert atmosphere;

[0070] S12, calcining the mixture in step S11 in a muffle furnace at 700° C. for 6 hours, then washing with distilled water to remove residues, and finally drying at 80° C. for 24 hours to prepare two-dimensional graphite phase carbon nitride g-C3N4 with different nitrogen vacancy concentrations;

[0071] S13, using a diamond anvil cell apparatus to generate compressive stress on the two-dimensional graphite phase carbon nitride g-C3N4 described in step S12.

[0072] The method for generating compressive stress on the two-dimensional graphite phase carbon nitride g-C3N4 in step S13 comprises the following steps:

[0073] S21. Prepare a pair of diamond and diamond base with a table diameter of 200 μm for centering and debugging, take T301 stainless steel sheet as sealing gasket, and perform a pre-pressing operation before sealing the sample;

[0074] S22, after the pre-pressing is completed, the pre-pressing indentation is punched by a laser punching device, the gasket aperture is cleaned by an ultrasonic instrument, and the sealing gasket is reset to the initial pre-pressing position as a sample cavity for loading the sample;

[0075] S23. Ruby powder is placed in the sample cavity for pressure calibration in the sample cavity. The sample is placed in the sample cavity and filled with sodium chloride powder as a pressure transmission medium.

[0076] S24. Pressurize the sample in the diamond anvil cell and use in situ high-pressure Raman spectroscopy to track the vibration mode and structural phase transition of the sample.

[0077] Comparative Example 1

[0078] The difference between Comparative Example 1 and Example 1 is that in step S11, the amount of KOH added is 0 g.

[0079] Figure 1 and Figure 2 The morphology and structure of the synthesized material are characterized. These characterizations prove that the two-dimensional graphite phase carbon nitride g-C3N4 material is synthesized in the present invention. It can be seen that g-C3N4 with nitrogen vacancies x The same layered and sheet-like structures are maintained as those of pristine g-C3N4. The electron diffraction pattern (inset) shows the in-plane hexagonal geometry of the sample with interfacial stacking. Figure 2 The XRD spectra of all samples in (d) show two major reflections at about 2θ = 12.8° and 27.7°, corresponding to the (100) and (002) crystal planes, respectively. With the increase of KOH content, the two peaks gradually weakened, indicating that the loss of ordered structure may occur during the thermal polymerization process. XPS analysis results show that g-C3N xThe samples largely retained the general structure, while KOH-assisted thermal polymerization successfully introduced nitrogen vacancies.

[0080] Figure 3 It is a basic schematic diagram of the diamond anvil press of the present invention.

[0081] Figure 4 These are the light absorption curves of the samples in Comparative Example 1 and Examples 1 to 3; it can be seen that as the nitrogen vacancy concentration increases, the absorption edge of the sample red shifts, indicating that the energy band of the electron has changed.

[0082] Figure 5 The band gap diagrams of the samples in comparative example 1 and examples 1 to 3 are shown in Figure 1. It can be seen that the band gap values ​​corresponding to the samples calculated by the Tauc diagram are as follows. The figure shows that the band gap value of the initial sample is 2.68 eV. With the introduction of nitrogen vacancies, the band gap narrows and the minimum band gap is 2.40 eV.

[0083] Figure 6 (a)-(d) are the Raman spectra of the samples in the comparative example and embodiments 1 to 3, respectively; it can be seen that the Raman spectra of g-C3N4 with different nitrogen vacancies during the pressurization process undergo an amorphous phase transition under pressure.

[0084] Figure 7 The photoluminescence pressure collection curves at the center of the samples in Comparative Example 1 and Examples 1 to 3 are shown. The comparison of the central wavelength shift of the photoluminescence spectrum of graphite phase carbon nitride with different nitrogen vacancy concentrations under high pressure is shown. It is obvious that the PL peaks of all types of samples undergo abnormal blue shifts at lower pressures, followed by continuous red shifts at subsequent pressures. The slight abnormal blue shift may be due to the introduction of nitrogen vacancies. The presence of nitrogen vacancies is conducive to pushing the effective valence band energy to a more negative value. The continuous red shift is due to the narrowing of the band gap caused by the contraction of the lattice under pressure. At the same time, by comparing samples with different nitrogen vacancy concentrations, it can be found that the introduction of nitrogen defects causes the absorption edge of the sample to red shift.

[0085] Figure 8 The color change of the sample in Example 1 under different pressures. It shows the color change of graphite carbon nitride in the sample cavity under different pressures. After pressurization, the micrograph shows that the color gradually deepens from yellow to orange and finally turns completely red. The color change of g-C3N4 after pressurization demonstrates the ability of pressure to regulate the optical properties of materials.

[0086] Fig. 9The dotted line graphs are the minimum pressures when the samples prepared in Examples 1 to 4 and Comparative Example 1 become amorphous. It can be seen that under high pressure, the interlayer coupling of the two-dimensional graphene carbon nitride changes under the action of pressure, and a pressure-induced amorphization phase transition occurs when the pressure reaches about 20 GPa. The pressure of the amorphization transition of the original graphene carbon nitride is about 25 GPa. With the introduction of nitrogen vacancies, the pressure point of the amorphization phase transition is advanced. The higher the vacancy concentration, the smaller the pressure point of the amorphization phase transition, from 24 GPa to 15 GPa, thereby achieving the regulation of the amorphous properties of the material.

[0087] In summary, the present invention provides a method for preparing a two-dimensional graphite phase carbon nitride g-C3N4 material. The method introduces nitrogen defects into g-C3N4 and applies pressure for synergistic effect, which can significantly reduce the band gap of the two-dimensional graphite phase carbon nitride g-C3N4 material and improve amorphization. At the same time, the concentration of nitrogen defects and the size of pressure are adjusted, and the original g-C3N4 and nitrogen-deficient g-C3N4 are systematically studied. x performance.

[0088] The above are merely exemplary embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for regulating the amorphous state and photoluminescence of g-C3N4 by nitrogen vacancies under high pressure, characterized in that: The following steps are involved: S11, fully grinding urea and KOH in a glove box protected by an inert atmosphere for 20 to 40 minutes; S12, continuously calcining the mixture described in step S11 in a muffle furnace, then washing with distilled water to remove residues, and finally drying at 80° C. for 24 h to prepare two-dimensional graphite phase carbon nitride g-C3N4 with different nitrogen vacancy concentrations; S13, using a diamond anvil cell apparatus to generate compressive stress on the two-dimensional graphite phase carbon nitride g-C3N4 described in step S12.

2. The method for regulating the amorphous state and photoluminescence of g-C3N4 by nitrogen vacancies under high pressure as claimed in claim 1, characterized in that: The mass ratio of urea to KOH in step S11 is 15:0.05-1.

3. The method for regulating the amorphous state and photoluminescence of g-C3N4 by nitrogen vacancies under high pressure as claimed in claim 1, characterized in that: The calcination temperature in the muffle furnace described in step S12 is 500-700° C., and the calcination time is 4-6 hours.

4. The method for regulating the amorphous state and photoluminescence of g-C3N4 by nitrogen vacancies under high pressure according to any one of claims 1 to 3, characterized in that: The specific operation method of using diamond countertops to generate compressive stress on two-dimensional graphite phase carbon nitride g-C3N4 in step S13 of claim 1 comprises the following steps: S21. Prepare a pair of diamond and diamond base with a table diameter of 200 μm for centering and debugging, take T301 stainless steel sheet as sealing gasket, and perform a pre-pressing operation before sealing the sample; S22, after the pre-pressing is completed, the pre-pressing indentation is punched by a laser punching device, the gasket aperture is cleaned by an ultrasonic instrument, and the sealing gasket is reset to the initial pre-pressing position as a sample cavity for loading the sample; S23. Ruby powder is placed in the sample cavity for pressure calibration in the sample cavity. The sample is placed in the sample cavity and filled with sodium chloride powder as a pressure transmission medium. S24. Pressurize the sample in the diamond anvil cell and use in situ high-pressure Raman spectroscopy to track the vibration mode and structural phase transition of the sample.

5. The method for regulating the amorphous state and photoluminescence of g-C3N4 by nitrogen vacancies under high pressure as claimed in claim 4, characterized in that: The pressure range of the pressurization in step S24 is 0 to 48 GPa.

6. The method for regulating the amorphous state and photoluminescence of g-C3N4 by nitrogen vacancies under high pressure as claimed in claim 4, characterized in that: A further preferred range of the pressurization pressure in step S24 is 15 to 24 GPa.